Ten‐year retrospective review (2003‐2013) of 56 inpatient admissions to stabilize elevated phenylalanine levels. Issue 1 (14th March 2019) - Clark, Anne; Merrigan, Christine; Crushell, Ellen; Hughes, Joanne; Knerr, Ina; Monavari, Ardeshir A.; Treacy, Eileen; Coughlan, Aoife
Abstract: Phenylketonuria (PKU) is an inherited metabolic disorder affecting phenylalanine metabolism. The Irish incidence is 1:4500. Currently, there are 500 patients under the care of the National Centre for Inherited Metabolic Disorders in Temple Street Children's University Hospital. Current practice is to admit PKU patients with phenylalanine (phe) levels that are consistently out of range despite an intensive multidisciplinary team input on an outpatient basis. The aim of this study was to evaluate changes in phe levels pre, during, and post admissions and to examine if there was a sustained impact post discharge. Fifty‐six patients were admitted between January 2003 and December 2013. Patients were all <18 years of age. Greater than 70% (n = 39) of the reasons for admission were due to multiple issues. Average admission time was 5 days. There was a significant decrease in median phe levels from prior to the admission to during the admission. However, there was a significant increase in median phe levels from during the admission (505 μmol/L) to both the 1‐6 months' and 7‐12 months' time points (618 and 651 μmol/L, respectively). The results highlight that while inpatient admissions can stabilize levels within the acute setting, this is not sustained long term. The ward environment does not accurately replicate home circumstances. This study highlighted that the reasons for admission are most often multifactorial, which is less likely to be resolved during a brief admission period.